2022
DOI: 10.3389/fenvs.2022.791052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heavy Metal Accumulation in Vegetables and Health Risk to Humans From Their Consumption

Abstract: Heavy metals contamination of soil and edible parts of vegetables is presently a challenging environmental issue worldwide. The present study determined the accumulated amount of cadmium (Cd), lead (Pb), nickel (Ni), cobalt (Co), zinc (Zn), copper (Cu), and manganese (Mn) in soil, coriander, onion, and tomato collected from agricultural fields of Jhansi city, India. The bio-concentration factor and non-carcinogenic health risks were also assessed to know the vegetables’ accumulation potential of heavy metals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 53 publications
4
16
0
1
Order By: Relevance
“…Our revisitation of the potential link between cycad-derived metal exposure and ALS-PDC comes at a time of increased contamination of human foods by heavy metals. Indeed, environmental pollution of metals and metalloids has emerged as a contemporary concern that impacts food security for much of the world [ 34 , 35 , 36 , 37 , 38 ]. As a result, the biotoxicity of metals in food has attracted attention from policy makers, health organizations, and the research community.…”
Section: Discussionmentioning
confidence: 99%
“…Our revisitation of the potential link between cycad-derived metal exposure and ALS-PDC comes at a time of increased contamination of human foods by heavy metals. Indeed, environmental pollution of metals and metalloids has emerged as a contemporary concern that impacts food security for much of the world [ 34 , 35 , 36 , 37 , 38 ]. As a result, the biotoxicity of metals in food has attracted attention from policy makers, health organizations, and the research community.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables such as Environmental Health Insights brinjal, gourd, spinach, coriander, tomato and pumpkin are particularly susceptible to heavy metal uptake by their roots, which can then be transported to the edible portions of the plant. 127,128 As a result, consuming these vegetables that contain heavy metals can be extremely hazardous to human health. Alexander et al 129 carried out research involving vegetables cultivated in soil contaminated with heavy metals.…”
Section: Effect Of Heavy Metal On Human Healthmentioning
confidence: 99%
“…Dim contaminated vegetables by selected metals in their diet. Gupta et al (2022) concluded that the THQ of all analyzed heavy metals in coriander, onion, and tomato was under the safe value of 1, indicating that consumption of these vegetables will not have any significant noncarcinogenic effects on consumers. These results were also supported by Balkhair and Ashraf (2016).…”
Section: Dim Of Heavy Metalsmentioning
confidence: 99%